Estado del arte sobre la implementación del modelo de gestión Lean manufacturing en la industria de alimentos (2018)
The aim of this study is to present the state of knowledge of Lean Manufacturing in the food industry, an industry that has characteristics (such as the perishability of its products, production in batches or difficult forecast of demand) that differentiate it from the rest of industries and make it more difficult to implement this management model. Initially, a bibliometric analysis of the documents published in relation to the object of study is carried out, analyzing the results by type of document, thematic area, number of documents published per year, countries and authors with the greatest number of publications made.